Journal of clinical rheumatology and immunology (Hong Kong Society of Rheumatology, 2019)
"The Journal of Clinical Rheumatology and Immunology (JCRI) is a peer-reviewed bi-yearly publication of The Hong Kong Society of Rheumatology. Before 2019, JCRI was published as "The Hong Kong Bulletin on Rheumatic Diseases". The journal's subject areas cover a wide range of Rheumatology and Immunological conditions from a clinical perspective"--